COHESION IN POEM A Case Study in `Marks` and `the way and the way things are` - Muhammad Rifqi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
This study is a linguistic analysis on literary works, especially of poem. It is mainly based on the study of cohesion given by Halliday and Hasan (1976). The study intends to describe how the cohesion works in two poems â€˜Marksâ€™ and â€˜the way and the way things areâ€™ written respectively by Linda Pastan and Nila Northsun. This is in line with Halliday and Hasan (1974:328) that a â€œlinguistic study of literature is not an interpretation of what the text means; it is an explanation of why and how it means what it does.â€ The cohesive devices realized in the poems were identified and the cohesive ties among them were, then, described to show why and how the two poems mean what they do.Keywords: poem, cohesion, cohesive devices, and cohesive ties